Eficácia da biomembrana de látex natural incorporada com extrato de Stryphnodendron barbatimam mart na cicatrização de úlceras cutâneas - Silva, Rosângela Gonçalves da [UNESP] (2015)
Latex biomembrane derived from the (Hevea brasiliensis) rubber tree has been used as dressing for cutaneous ulcers and studies on its utilization as an extended liberation system to carry bioactive compounds capable of accelerating and activating the process of tissue wound healing, are increasingly being undertaken. The slow healing features the chronicity of the wound and it occurs in the wound closure absence or failure, exceeding the physiological healing period of 2 to 3 weeks. The reasons for such change are local and systemic disorders. This study was carried out to assess the effectiveness and safety of chronic ulcer treatment by using the natural latex biomembrane derived from the Hevea brasiliensis rubber tree incorporated with the Stryphnodendron barbatimam Mart (barbatimão) extract. In the research 45 patients were selected, they were suffering from chronic ulcers of different etiologies, age between 35 and 90, registered in the National Health System (SUS) and under the care of their respective health care unit. Those subjects were divided into three groups comprising 15 patients each who were treated along a minimum period of 30 days which began in April 2014, and they were characterized as G1 test group- natural latex biomembrane combined with barbatimão extract, with 1 exclusion; G2- natural latex biomenbrane, with 7 exclusions; and G3- barbatimão extract, with 10 exclusions. Besides the dressings, sample collections were carried out for sowing in selective environments, showing that despite the presence of microorganisms there was no interference in wound healing. The dressings made from combined biomembrane yielded better results not only in wound healing, but also in controlling and reducing microorganism colonies, in comparison with the other control groups. The results found surely provide subsidies for future ... (Complete abstract click electronic access below)